Mechanical Properties of Alkali Activated Fly Ash Geopolymer Stabilized Expansive Clay - Murmu, Anant Lal; Jain, Anamika; Patel, Anjan (KSCE Journal of Civil Engineering, 2019)
It has always been a challenge for civil engineers to lay roads in the areas covered by expansive soil. The expansive soil undergoes extreme phase changes from being hard in hot summer to being slushy and without strength in monsoon season. Thus, the engineering properties of the expansive soil must be improved before laying the roads. This paper presents the results of experimental work carried out to improve the engineering properties of an expansive clay i.e. black cotton soil (BCS) by using fly ash geopolymer. Sodium hydroxide (NaOH) and sodium silicate (Na 2 SiO 3 ) solutions were mixed in different ratios (0.5, 1, 1.5, and 2) and used for synthesizing the geopolymer. The stabilized BCS samples were characterized in the laboratory for various properties viz., Atterberg’s limits, free swell ratio, and unconfined compressive strength. The untreated and treated BCS samples were also analyzed for their microstructural and morphological properties by using the SEM (scanning electron microscope) images and the XRD (X-ray fiffractometer) and FTIR (Fourier-transform infrared spectroscopy) spectra. An increase in the unconfined compressive strength and reduction in free swell ratio as well as shrinkage limit was observed after stabilization with geopolymer. Results also indicate binding of soil particles and formation of dense microstructure resulting in higher strength and less swelling and shrinkage characteristics. Furthermore, the bender element test was used to indicate the improvement in stiffness of the geopolymer stabilized expansive soil in terms of shear wave velocity.